Eco-theological anthropology in Christianity: imago Dei and ecological preservation - Ismail Lala (HTS Teologiese Studies/Theological Studies)
Genesis 1:26 states that humankind has been created in the image of God. There are three general interpretations of what this means. While the substantial view emphasises the essence of humankind and the relational view underscores the social aspect, the functional view highlights the responsibility of humankind to God’s creation. Recent studies have suggested that the substantial view was dominant in the pre-modern period and the functional view has become more popular in contemporary Christian theology.